Sejarah Sosial Pendidikan Islam Masa Kolonial Belanda (1602-1942) dan Jepang (1942-1945) - Rochim, Achmad Syainur; Zulfi Mubaraq; M. Samsul Hady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Introduction: The study of the social history of Islamic education during the Dutch colonial period (1602-1942) and Japan (1942-1945) is very important to be studied in more depth. This is because the study never stops being debated. The purpose of this paper is to understand 3 things: First, the paradigm of that period consists of: goals, materials, methods and mursyid and students. Second, internal and external factors that influence it. Third, the positive and negative implications of the theme for Indonesian society. The method used is a literature review with an article review approach based on Harold Lasswell's theory, data collection using literature review procedures and content analysis techniques. The results found 3 things: First, the paradigm of the Social History of Islamic Education during the Dutch Colonial Period has 5 forms: (1) Objectives: preparing educated personnel as low-level or manual laborers, limiting the development of Islamic education and westernization and Christianization. (2) Materials: general knowledge, religion, bare books, foreign languages, new systems and methods introduced by the Dutch. (3) Method: dichotomous and discriminatory education system, Collective learning or individual learning. (4) Mursyid: scholars or teachers with a Dutch educational background. (5) Students: public school students. During the Japanese colonial period, there were 5 forms: (1) Objectives: eliminating the influence of western culture, supporting Japan's war interests and spreading the influence of Japanese culture and ideology. (2) Material: religious knowledge, Indonesian, Japanese, Nippon Seisyin, Hakko Ichiu doctrine (Loyalty to Japan), military activities, Earth science with a geopolitical and agricultural perspective and Japanese customs. (3) Method: eliminating the dichotomous education system, implementing inclusive education, standardizing the education system. (4) Mursyid: teachers who were burdened by the Hakko Ichiu doctrine, and several educational figures such as Ki Hajar Dewantara, K.H. Zainal Arifin, K.H. Wahid Hasyim, Kahar Muzakkir and Bung Hatta as well as K.H. Hasyim Asy'ari. (5) students: everyone including children of officials and ordinary people. 1 Pendas : Jurnal Ilmiah Pendidikan Dasar, ISSN Cetak : 2477-2143 ISSN Online : 2548-6950 Volume XX Nomor XX, Bulan Tahun Second, internally, the Dutch colonial period influenced: (1) the low quality of human resources in Islamic education (2) a diverse education system (Hindu-Islamic, surau, Islamic boarding school) (3) the spirit of patriotism and the Islamic renewal movement. While externally: (1) discrimination and obstacles to Islamic education, (2) the implementation of ethical politics that provided some leniency, (3) teacher ordinances limiting the activities of religious teachers. Meanwhile, during the Japanese colonial period, internally, there were: (1) changes in the orientation of Islamic education (spiritual to worldly), (2) demonstrations and resistance from the santri community, (3) innovations in madrasah management and curriculum. While externally: (1) looser policies towards Islamic education, (2) the closure of several schools and madrasahs, (3) the orientation of education for the interests of the Japanese military. Third, the positive implications of the social history of Islamic education during the Dutch colonial period were: (1) inspiration for the establishment of madrasahs, (2) modernization of Islamic education, (3) introduction of a more organized education system, (4) the emergence of awareness of the importance of formal education for the natives. Meanwhile, the negative implications are: (1) discrimination and restrictions on Islamic education, (2) a dualistic educational system that is detrimental to indigenous people, (3) exploitation and oppression of society through educational policies, (4) the hegemony of Western education. During the Japanese colonial period, the positive implications were: (1) the development of more progressive Islamic education, (2) the abolition of the caste system and increased access to education, (3) increased political awareness and nationalism among Muslims. Meanwhile, the negative implications are: (1) instability of the educational system due to changes in the system by the colonial government, (2) a general decline in the quality of education, (3) the instrumentalization of education for Japanese political interests. The conclusion of this paper shows that during the Dutch period, Islamic education experienced discrimination but actually encouraged indigenous awareness of the importance of formal education. During the Japanese period, Islamic education experienced more relaxed access but was directed towards Japanese political interests.